Humanized care; the case of patients subjected to chemotherapy - Luz Viviana Grisales-Naranjo; María Mercedes Arias-Valencia (Universidad de Antioquia, 2013)
Objective. Herein, we seek to know the necessities of humanized care of patients subjected to chemotherapy. Methodology. The study was carried out with patients, of both sexes, diagnosed with different types of cancer who received chemotherapy treatment in an oncology unit of the city of Medellín, Colombia during 2011. A qualitative approach was used with tools from grounded theory; 23 interviews were conducted and a field diary was kept. During the analysis, codes were extracted that were subsequently grouped into categories that best represented the phenomenon studied. Results. Cancer patients subjected to chemotherapy have needs for humanized care. The emotional, spiritual, social, and affective necessities were highlighted as a consequence of the impact of the news of the diagnosis and the notorious physical changes confronted by these patients. The category of dehumanization of care emerged related to the information of the diagnosis and in the communication the personnel maintained with these patients. Conclusion. The cancer patient receiving chemotherapy is a seriously ill person, with necessities, who requires humanized care by the healthcare provider personnel.